WHAT ARE THE AFFECTING FACTORS ON ENVIRONMENTAL DISCLOSURE ON THE COMPANIES? - Sari Mujiani; Median Wilestari; Aprilia Diah Astuti (Mediastima, 2021)
The aim of this study is to determine affecting factors on Corporate Environmental Disclosure on Go Public companies listed in PROPER from 2015 to 2019. Companies with gold and green ranking and listed in PROPER are included the population in this study. This phrase could be omitted, samples were taken using a purposive sampling method with specific parameters. The findings of this research show that: (1) The size of the Audit Committee has a positive impact on the occurrence of corporate environmental disclosure. This is because if the number of audit committees within an organization exceeds the number of requirements set, it will lead to increased supervision and company controls to ensure that the expected environmental disclosures are made. (2) Managerial ownership has a negative impact on the occurrence of corporate environmental disclosure, indicating that the size of a company's managerial share ownership has little bearing on the company's environmental disclosures. (3) The incidence of corporate environmental disclosure is unaffected by environmental results. This explains why environmental success has had little effect on companies that are featured prominently in the PROPER ranking, allowing the public to better recognize and support the company's efforts.